Kajian Perilaku Swamedikasi Menggunakan Obat Penggemuk Badan Oleh Pasien Pengunjung Apotek Di Kota Kupang Tahun 2016 - Maria Yangsye Lenggu (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2017)
Community efforts to treat themselves are known as self-medication. Self-medication is usually done to treat complaints and minor ailments. The Sudan Journal of Rational Use of Medicine (2014) found 7 categories of drugs most widely used in self-medication, one of which is a body fat drug. Self-medication acts tend to increase. Like whether self-medication behavior uses body fat drug performed by pharmacy visitors in Kupang city? The purpose of this research is to determine the prevalence, behavior, and perception of self-medication patients using body fat drug. This research is a descriptive observational study with the subject inclusion criteria. Pharmacy visitor patients who buy body fat medicine for self-medication. The study was conducted in August - October 2016. Data collection tools were questionnaires with 60 questions covering 37 Likert scale questions distributed in 10 pharmacies. The questionnaire returned was 108. The study of self-medication behavior with prevalence indicators was 48.15% had purchased/used the drug in the past 1 month, 32.41% self-medication for me, 21.30% 2 times/ treatment period, 35.19% used dexamethasone drugs, livron B plex and pronicy. Study with behavioral indicators, as much as 62.04% of respondents knew the body fat drug, 37.96% of respondents got drug information from friends, 45.37% bought at the pharmacy, complaints that were treated were not ideal body weight (thin / bb down) and no appetite, experienced complaints for 1 week -> 20 years, 5.56% do self-medication for reasons that are cost-effective, many friends use and prove and 4.63% faster to obtain at low cost. A study with perception indicators, 75% said it was important to consider the recommendation of the pharmacist, 92.59% of patients wanted the drug to be used safely, 68.52% of respondents did self-medication because they had increased appetite and the body became fat to take the drug. as many as 81.48% of respondents said that the body's fattening drugs can increase appetite.